1999
DOI: 10.1111/j.1708-8305.1999.tb00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidiosis in Travelers with Diarrhea from the Tropics

Abstract: Available data is too limited to affirm that residence or travel in tropical countries increases the risk for microsporidial infection, but the cases presented here suggest that E. bieneusi could be a cause of self-limited diarrhea in immunocompetent travelers returning from the tropics or could chronically affect immunocompromised HIV-infected travelers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 21 publications
2
42
0
2
Order By: Relevance
“…In reference to the presence of microsporidia in Spain, they have mainly been reported to occur in HIV/AIDS patients (8-10) but also in HIV-negative individuals, including travelers (26), elderly people (27), and the immunocompetent population (1). In most of these studies, E. bieneusi was the microsporidian responsible for clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In reference to the presence of microsporidia in Spain, they have mainly been reported to occur in HIV/AIDS patients (8-10) but also in HIV-negative individuals, including travelers (26), elderly people (27), and the immunocompetent population (1). In most of these studies, E. bieneusi was the microsporidian responsible for clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have reported intestinal infections caused by E. intestinalis in Africa (8,9,13). Some cases have been described in immunocompetent patients, notably in adult travelers and in young children (16,12). Two systematic surveys in Niger (3) and Zambia (12) showed the low prevalence of microsporidia in children: 0.8 and 0.56%, respectively.…”
mentioning
confidence: 99%
“…Most cases of human microsporidiosis are associated with immunosuppression, but increasing numbers of cases in non-HIV-infected immunocompetent patients are reported. These reports include infections of travelers to developing countries as well as infections of residents of various tropical countries (1,5,6,11,13,14,17,(19)(20)(21)23). Only a few studies examined the role of microsporidia in returning travelers.…”
mentioning
confidence: 99%